Heat Exchanger for Bio-Digester under Thermophilic Range - Sapkota, Prajwal; Poudel, Laxman (Journal of Advanced College of Engineering and Management, 2019)
Bio-gas has been one of the sources of renewable energy and has been used from long time. It is produced by the anaerobic digestion or decomposition of organic compounds and has different process. The digestion process is carried out by bacteria present in the waste and it is highly dependent on the bacteria which work differently on different temperatures. The rate of anaerobic digestion is highest at hemophilic temperature (55°C). Similarly, it is moderate at mesophilic temperature (35°C) and is lowest at psychrophilic (below 20°C). Thus, to attain the highest digestion rate a thermophilic heating system has beend eveloped. The heating system uses five heat exchangers to heat the influent at digester which is of 35m3 volume, to maintain temperature at 56°C. The volume of bio-gas production from this system which uses cow dung as digestingmaterial is about 28 m3 per day.